Public Feeding Interactions as Enrichment for Three Zoo-Housed Elephants - Fernandez, Eduardo J. (Animals (Basel), 2021)
SIMPLE SUMMARY: Human–animal interactions are an important focus of modern animal welfare research. A subset of this interest includes animal–visitor interactions that occur in zoos. One understudied aspect of animal–visitor interactions involves public feedings, where visitors can directly feed the zoo animals. We examined the effects of public feedings compared with nonpublic feed days on the general activity of three zoo-housed elephants. In addition, we examined the general activity of the elephants in the months prior to public feedings, as well as their general activity on public feed days before, during, and after a public feeding. Public feedings were effective at increasing social activity and decreasing stereotypies for two of the elephants when compared with nonpublic feed days. Additionally, all three elephants showed increased foraging and decreased inactivity following a public feeding. Our results suggest that public feedings can be an effective form of environmental enrichment for zoo-housed elephants. ABSTRACT: The past few decades have seen increased interest in studies examining the welfare of elephants and animal–visitor interactions. One understudied area for both pursuits is the impact of public feeding interactions. Our study examined the effects of public feedings on the general activity of three zoo-housed elephants. Prior to public feedings, we developed and assessed a 21-behavior ethogram split into six classes of behavior. Comparisons between the elephants demonstrated that only one of the elephants engaged in stereotypies with regularity (>30%), and that the stereotypies occurred in place of most foraging. During public feedings, we compared the general activity of each elephant independently and across both public feeding and nonpublic feeding days, as well as the general activity before, during, and after a public feeding. Public feedings increased social activity and decreased stereotypies when compared with nonpublic feeding days for two of the elephants. In addition, all three elephants showed increased foraging and decreased inactivity in the period after a public feeding session. These results demonstrate that public feedings can be a useful tool for enriching the welfare of zoo-housed elephants and are among the first sets of data to demonstrate positive welfare outcomes associated with public feedings.